Introduction - Plakotos, Giorgos; Syriatou, Athina (Historein, 2018)
Three historiographical articles, an essay on the press in nineteenth-century Finland and an analysis of a historical novel comprise this issue of Historein. Two of them analyse the historiography of the Greek interwar period as it concerns the economy and notions of national cultural identity, respectively. Another article discusses the impact of digital archiving for the historical profession, contemplating on its responsiveness to the demand for "instant history". The field of digital humanities also informs the next article, which, through the example of the Finnish press, seeks to make the concept of the virtual relevant in historical research. The final article gives a Foucauldian analysis of the notion of parrhesia for two historical personalities as they emerge from a well-known nineteenth-century historical novel, examining the multiple levels of historicity of the personas of the novel as well as the intentions of the critical views of the writer of his contemporary historical conflicts.